2023
DOI: 10.1155/2023/6692810
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polycyclic Aromatic Hydrocarbons Urine Metabolites with Type 1 Diabetes

Abstract: Purpose. Polycyclic aromatic hydrocarbons (PAHs) are believed to be a possible factor in the development of cancer, ischemic heart disease, obesity, and cardiovascular disease. The objective of this study was to explore the association between certain metabolites of urinary PAH and type 1 diabetes (T1D). Methods. In Isfahan City, a case-control study was carried out involving 147 T1D patients and an equal number of healthy individuals. The study measured the levels of urinary metabolites of PAHs, specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…These findings suggest that AHR signaling activation, depending on the immune cell type, is immunosuppressive and can modulate immune responses during T1DM development, highlighting the potential of AHR targeting in T1DM. In contrast to the role of AHR in T1DM, a recent study reported that high levels of urinary metabolites of polycyclic aromatic hydrocarbons (PAHs) are associated with an increased risk of T1DM in children and adolescents [126]. In animal studies, prenatal exposure to a mixture of PAHs resulted in dysfunctional pancreatic islets associated with T1DM [127].…”
Section: Type 1 Diabetes Mellitus (T1dm)mentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that AHR signaling activation, depending on the immune cell type, is immunosuppressive and can modulate immune responses during T1DM development, highlighting the potential of AHR targeting in T1DM. In contrast to the role of AHR in T1DM, a recent study reported that high levels of urinary metabolites of polycyclic aromatic hydrocarbons (PAHs) are associated with an increased risk of T1DM in children and adolescents [126]. In animal studies, prenatal exposure to a mixture of PAHs resulted in dysfunctional pancreatic islets associated with T1DM [127].…”
Section: Type 1 Diabetes Mellitus (T1dm)mentioning
confidence: 99%
“…The role of AHR as a molecular interface between EDC exposure and the development of various pancreatic diseases, including cancer, is summarized below (Figure 3). are [124][125][126][127], T2DM [138][139][140][141][142][143][144][145][146], acute pancreatitis [157][158][159][160], chronic pancreatitis [161], and pancreatic cancer [167][168][169][170][171][172][173]. are [124][125][126][127], T2DM [138][139][140][141][142][143][144][145][146], acute pancreatitis [157][158][159][160], chronic pancreatitis [161], and pancreatic cancer [167][168][169]…”
Section: Role Of Edc-regulated Ahr In Pancreatic Cancermentioning
confidence: 99%
See 1 more Smart Citation